Does Neck Disability Index Correlate With 12-Month Satisfaction After Elective Surgery for Cervical Radiculopathy? Results From a National Spine Registry. Issue 5 (3rd July 2019) - Khan, Inamullah; Sivaganesan, Ahilan; Archer, Kristin R; Bydon, Mohamad; McGirt, Matthew J; Nian, Hui; Harrell, Frank E; Foley, Kevin T; Mummaneni, Praveen V; Bisson, Erica F; Shaffrey, Christopher; Harbaugh, Robert; et al.
Abstract: BACKGROUND: Modern healthcare reforms focus on identifying and measuring the quality and value of care. Patient satisfaction is particularly important in the management of degenerative cervical radiculopathy (DCR) since it leads to significant neck pain and disability primarily affecting the patients' quality of life. OBJECTIVE: To determine the association of baseline and 12-mo Neck Disability Index (NDI) with patient satisfaction after elective surgery for DCR. METHODS: The Quality Outcomes Database cervical module was queried for patients who underwent elective surgery for DCR. A multivariable proportional odds regression model was fitted with 12-mo satisfaction as the outcome. The covariates for this model included patients' demographics, surgical characteristics, and baseline and 12-mo patient reported outcomes (PROs). Wald-statistics were calculated to determine the relative importance of each independent variable for 12-mo patient satisfaction. RESULTS: The analysis included 2206 patients who underwent elective surgery for DCR. In multivariable analysis, after adjusting for baseline and surgery specific variables, the 12-mo NDI score showed the highest association with 12-mo satisfaction (Waldχ2-df = 99.17, 58.1% of total χ2). The level of satisfaction increases with decrease in 12-mo NDI score regardless of the baseline NDI score. CONCLUSION: Our study identifies 12-mo NDI score as a very influential driver of 12-mo patient satisfaction after surgery for DCR. In addition, there are lesser contributions from other 12-mo PROs, baseline Numeric Rating Scale for arm pain and American Society of Anesthesiologists (ASA) grade. The baseline level of disability was found to be irrelevant to patients. They seemed to only value their current level of disability, compared to baseline, in rating satisfaction with surgical outcome. Graphical Abstract: